Woolworths SA : something in the yoghurt mix - Bowen, Amanda; Abratt, Russell ([London] : SAGE, 2016)
In May 2008, alerted by a primary dairy supplier that one of its raw material suppliers may be including gelatine in its products, Julian Novak, divisional director of food at Woolworths SA, tasked his team to investigate the issue. The allegations proved to be true. There was gelatine in Woolworths' entire yoghurt range. In 2003, the company had agreed to ensure that its yoghurts were free of gelatine (a product derived from meat sources), and had therefore advertised them as such. Novak wondered how to act to preserve the company's reputation and what action should be taken.
Originally Published in: Bowen, A. & Abratt, R. (2009). Woolworths SA: Something in the Yoghurt Mix. WBS-2009-18. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Woolworths; Customer relations -- Management -- Case studies; Marketing -- Case studies; Crisis management -- Case studies